Southwest Pueblo quadrangle, Colorado--Pueblo Co., 1998 : 7.5 minute series (topographic) - 3956 Geological Survey (U.S.) (Reston, Va. : The Survey ; Denver, Colo. : For sale by the Survey, 1999)
Learn how to use topographic maps to determine elevations, landform types, and principles of scale and location. Also, learn how to draw contour lines and how to construct topographic profiles